CrossFit Training Impact on the Level of Special Physical Fitness of Young Athletes Practicing Judo - Aleksander Yurevich Osipov; Roman Sergeevich Nagovitsyn; Fanavi Haybrahmanovich Zekrin; Fendel' Tatyana Vladimirovna; Dmitry Alexandrovich Zubkov; Tatyana Vladimirovna Zhavner (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
The high level of individual physical fitness of athletes is one of the main factors in achieving sports success in martial arts. This study aimed to assess CrossFit training's impact on the level of physical fitness of young (16-17 years old) athletes practising judo. The athletes' competitive activity data was also assessed. The young athletes (n=33) demonstrated athletic performance at a level approaching that of elite athletes. They were randomly divided into approximately two equal groups. During the training of one of the groups (n=16), CrossFit sessions were used. The obtained data were evaluated using SJFT, the level of lactate concentration in blood and a comparative analysis of the judoists' competitive coefficients (CC). Statistical analysis was performed using the Mann-Whitney U-test. A significant (p<0.05) athletic superiority has been revealed among those who used CrossFit training in the coefficient of active combat time (СС-3) in competitive matches. SJFT indicators of both athlete groups show a positive trend. Increased dynamics of blood lactate concentrations after exercises were detected among both groups. Moreover, among the athletes who used CrossFit training, blood lactate level data were significantly (p<0.05) higher, averaging 14.54±0.51 mmol/l. The duels percentage won by athletes who used CrossFit training was considerably higher than those athletes who did not use CrossFit training (59% vs 54%).